The Biblical lyric of Benito Arias Montano in its European and Spanish contexts - Czepiel, M (Brill Academic Publishers, 2024)
The lyric poetry of the Spanish humanist Benito Arias Montano (1527–1598) has been called “the culmination of Neo-Latin poetry in Spain”; however, there is a dearth of scholarship on his collections of original lyric poetry, Humanae salutis monumenta (1571) and Hymni et secula (1593). In this study, I aim to situate these works in the context of early modern European ‘biblical poetry’ and Spanish Christian Horatianism. I explain that Arias Montano’s biblical poetry is exceptional since inquisitorial censorship in Spain had stifled vernacular poetry on biblical themes, a prohibition he overcame by writing in Latin. I go on to show how, while Arias Montano is part of the European trend of poetic versions of what were considered the ‘poetic’ biblical books, in his original poetry he departs from these trends. Rather, his original lyric constitutes an innovation in the field of versified outlines of the Bible. I argue that this was possible due, among other factors, to the Renaissance reception of Horace. Finally, I also demonstrate how his biblical poetry is markedly different from vernacular Christian Horatianism in Spain with its preference for moral-philosophical themes.